The health and safety of diatom blooms / Alyssa Safiyah Abd Malek ... [et al.] - Abd Malek, Alyssa Safiyah; Noor Hisham, Aida Qasrina; Hisham, Nur Hafizah; Rahizar, Nurshahirah; Abdul Aziz, Nur Syawanie; Shukor, Siti Nur Shazwani; Jamaludin, Siti Nur Syifaa; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Plankton is a collection of drifting and floating organisms in water that cannot move against currents or winds (Britannica, 2023). There are several types of plankton. Usually, plankton can be identified based on its size, type, and duration of drifting. It can be observed under the microscope. There are two basic groups of plankton which are phytoplankton (plants) and zooplankton (animals). Phytoplankton are microscopic marine algae. This phytoplankton has chlorophyll and needs light for its growth development.